2020
DOI: 10.3389/fneur.2020.564431
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Stress Coping in Awake Bruxism

Abstract: Numerous studies have analyzed the relationship between psychological factors and bruxism. However, the data are often obscured by the lack of precise diagnostic criteria and the variety of the psychological questionnaires used. The purpose of this study is to determine the association between awake bruxism and psychological factors (anxiety, depression, sociability, stress coping, and personality traits). With this aim, 68 participants (13 males) completed a battery of psychological questionnaires, a self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…This may be due to stress that many dental students experience during their studies [ 31 , 32 ]. Soto-Goni et al [ 33 ] showed that subjects with awake bruxism show larger levels of anxiety, somatization, and neuroticism but also display more adapted coping strategies than TMD patients. The authors suggested that AB may play a positive role in stress coping, which would be compatible with the hypothesis of mastication as a means of relieving psychological tension.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to stress that many dental students experience during their studies [ 31 , 32 ]. Soto-Goni et al [ 33 ] showed that subjects with awake bruxism show larger levels of anxiety, somatization, and neuroticism but also display more adapted coping strategies than TMD patients. The authors suggested that AB may play a positive role in stress coping, which would be compatible with the hypothesis of mastication as a means of relieving psychological tension.…”
Section: Discussionmentioning
confidence: 99%
“…13 Another study showed that participants with awake bruxism had significantly higher levels of trait and state anxiety. 44 These results indicate that awake bruxism would play a role in reducing stress and anxiety, since certain people who perceive situations as threatening or stressful display this behavior more frequently. 45 A statistically significant association between sleep bruxism and anxiety was found, coinciding with findings from a Finnish study, where it was concluded that anxiety would be acting as a risk factor for sleep bruxism.…”
Section: Discussionmentioning
confidence: 90%
“…Surprisingly, it has been proven that the mere occurrence of bruxism symptoms can also bring positive side effects in certain medical conditions. For example, patient with gastro-esophageal reflux will have a significantly decreased risk of teeth wear due to an increased salivation caused by bruxism [7].…”
Section: Symptomsmentioning
confidence: 99%
“…Although it is reported that such hyperactivity of masticatory muscles varies in etiology, the prevalence of both types of bruxism significantly decreases with age [6]. A study among young college students demonstrated that 37.9% of them struggle with awake bruxism and 31.8% of them also deal with sleep bruxism [7].…”
mentioning
confidence: 99%